Regulating for social and environmental sustainability: A stakeholder perspective from the Bahamian spiny lobster fishery. (February 2021) - Doerr, Angee N.
Abstract: Lobster condos, artificial habitats used as aggregation devices, are the predominant collection tool for commercial fishers in The Bahamas. Despite the fact that deployed lobster condos are in excess of a million, there has not been a study focusing on how or why local fishers are using these artificial habitats, or how they should be managed. Currently, the Bahamian government is considering the creation of new laws to regulate the use of condos within national waters. The Bahamian spiny lobster fishery is not currently deemed overfished, but there is uncertainty regarding lobster populations, current fishing methods, and successful management strategies. Although Maritime Stewardship Council certification was granted in 2018, more information on condo use and overall monitoring was deemed necessary. In this paper, we investigate fisher beliefs regarding current and potential regulations, and propose management strategies for the Bahamian spiny lobster fishery. Through informal interviews and semi-structured surveys, we examined the use of lobster condos by fishers, and stakeholder beliefs on regulating lobster condos and the lobster fishery more broadly. We found general support for regulating the use of condos, but island-level trends in the type of condo restriction supported. This research can be used to inform the policy process in The Bahamas as existing regulations are revised and new laws are developed, and can influence policy creation in similar small island fisheries. Highlights: Marine Stewardship Council certification enhances fishery export competitiveness. Effective fishery regulation requires enforceability and social sustainability. Caribbean nations are underrepresented in sustainability certifications. Understanding stakeholder perspectives improves management outcomes.